Penerapan Model Pembelajaran Student Facilitator Explaning dalam Ilmu Tajwid untuk Meningkatkan Keberhasilan Peserta Didik dalam Membaca Al-Qur’an Kelas VII MTs.NW Sepit - Zakaki, Zakaki (Lembaga Yasin AlSys, 2021)
This study aims to: (1) To determine the level of understanding of Class VII students at MTs. NW Sepit in learning Tajwid using the Student Facilitator and Explaining (SFE) learning model to find out the process of applying the student facilitator explaning learning model in tajwid science to increase the success of students in reading the Qur'an class VII at MTs. NW Sepit (2) To find out the process of applying the student facilitator explaning learning model in tajwid science to increase the success of students in reading the Qur'an class VII at MTs. NW Sepit. The research approach used is a type of quantitative approach. In collecting data using the method of Documentation, Interview (Interview), Test and Observation. The analysis technique uses descriptive qualitative, namely to describe the data that has been obtained so that it will describe the actual reality according to what happened in the field. The results of the study show that the application of the student facilitator explaining learning model for students at MTs NW Sepit can be categorized as good, this is evidenced by the increased ability of students to read the Qur'an properly and correctly. Supporting factors include: good teacher quality, student activity, application of learning methods and a conducive environment.